An extensive study on the chemical diversity of lipophilic extractives from Eucalyptus globulus wood. (December 2020) - Gominho, Jorge; Lourenço, Ana; Marques, António Vélez; Pereira, Helena
Abstract: Three mature Eucalyptus globulus trees with 40 years of age were studied at three height levels (0%, 35%, and 60% of total tree height) and at three radial regions (sapwood, inner and outer heartwood). The composition of lipophilic extracts was evaluated and an extensive list of 202 compounds was reported for the first time. The fatty acids were the major chemical family, representing 40.8% of the total compounds, followed by phytosterols (19.0%), aromatics (10.5%) and triterpenes (10.4%). Saturated fatty acids accounted for 74.2% of total compounds (C16:0, C24:0 and C26:0 were predominant), β-Sitosterol and stigmastanol were the main sterols (80 and 7% respectively), while aromatics were mainly represented by syringic acid, 4-hydroxy-3, 5-dimethoxybenzaldehyde, vanillic acid, and vanillin. The main triterpenes were asiatic and arjunolic acids. Graphical abstract: Image 1 Highlights: Lipophilic extracts of mature wood of Eucalyptus globulus included 181 compounds. The main chemical families were fatty acids, sterols, triterpenes and aromatics. Homologous series of fatty acids, alcohols and alkanes ranged from C10 to C30. Fatty acids accumulated at stem base and heartwood, triterpenes at the top and sapwood.